Public Willingness to Pay for and Participate in Sanitation Infrastructure Improvement in Western China's Rural Areas - Wu, Simei; Zhang, Yang; He, Bao-Jie (Frontiers in Public Health, 2022)
Suitability and feasibility of PPP pattern in rural contexts has not been well documented and understood. To address this research gap and practical plight, this study aims to analyze the rural resident’s willingness to pay for and participate in the improvement of rural sanitation facilities and further explore the drivers and barriers affecting their decisions. This study was conducted in the rural areas of three western provinces including Shaanxi, Ningxia and Inner Mongolia western China’s rural areas through the questionnaire of 1,248 rural residents. The results indicate that 30.15-57.82% of the respondents would like to pay for sanitation improvement and 66.74-70.96% of the respondents could provide labor. In Inner Mongolia, the proportion of respondents who were willing to pay was the highest, while the proportion of respondents who may provide labor was the lowest among the three provinces. Respondents of Ningxia had the least willingness to pay, and respondents of Shaanxi had the highest willingness to participate. The binary logistical regression analysis further indicated that factors which affected respondents’ decisions varied with province. Overall, respondents’ rural (living) duration time, associated with rural-urban migration patterns, personal interest in local government notice and the latest time when the sanitation facilities was improved, could significantly affect their willingness. In Inner Mongolia, occupation and water availability could significantly influence respondents’ willingness, and both gender and health conditions had notable impacts. In Ningxia, respondents’ personal interest in local government notice had a significant impact on the willingness, and low-income respondents showed a more notable willingness to pay and participate. In Shaanxi, occupation and water availability could significantly influence respondents’ willingness. Respondents’ personal interest in local government notice had a notable impact on their willingness. The results highlight the significant performance of a sanitation policy that is customized based on local socioeconomic status. This study is of significance to understand rural resident’s participation in sanitation infrastructure improvement to support relevant PPP projects and is important to solve poverty-caused dilemma.